Hydrogen interaction characteristics of a Cr2O3Y2O3 coating formed on stainless steel in an ultra-low oxygen environment. (29th March 2019) - Wang, Jipeng; Ling, Yunhan; Lu, Zhaoxia; Zhang, Mengyuan; Zhou, Qingyun; Wang, Rongguang; Li, Yunhui; Zhang, Zhengjun
Abstract: Ceramics are the most promising candidates for tritium permeation barriers for fusion reactors due to their high thermal and chemical stabilities and low hydrogen isotope permeation reduction factors. However, hydrogen embrittlement and a large number of defects in ceramic coatings are new challenges for first wall materials in nuclear reactors. To address this issue, a new Cr2 O3 Y2 O3 coating with a thickness of about 100 nm was synthesized and placed in an ultra-low oxygen partial pressure (8 × 10 −20  Pa) environment, in which a compact CrY alloy coating was successfully deposited on the stainless-steel substrate by pulsed electrochemical deposition. The interactions between the coating and hydrogen plasma were comprehensively analyzed and compared via surface analysis techniques, including TEM, XPS and electrochemical impedance spectroscopy (EIS). The mechanical properties of the coating before and after hydrogen permeation were studied by tensile testing. It was found that this ceramic coating effectively reduced the defect concentration and retained a high protective performance upon hydrogen exposure. Therefore, this new Cr2 O3 Y2 O3 coating has potential as a promising hydrogen permeation barrier. Graphical abstract: Image 1 Highlights: The Cr2 O3 Y2 O3 coatings were successfully synthesized in an ultra-low P o2 . This new coating effectively reduced the Cr vacancies due to the presence of Y ions. Improved hydrogen permeation resistance and the tensile strength of the SS have been obtained.